Rancang Bangun Data Logger Temperatur - Agus Dwi Korawan (SIMETRIS, 2018)
Temperature data logger is a portable measurement instrument used for reading the temperature of an object and storing the results of temperature in the form of data. Temperature data logger consists of NTC 7.5 K probe thermocouple with serial number SSR038 (16 pieces), the arduino mega microcontroller atmega 2560, and the card data logger module SC-MMC with serial number MOD009. The software used is Arduino 1.5.7 windows based. Testing of 16 thermocouples is done by dipping the thermocouple in water with an initial temperature of about 27oC, then the water is heated slowly for 650 seconds. The results show the same chart pattern, even though there is a slight difference in value. Maximum deviation is 1.0oC. The temperature which is displayed on the monitor screen and stored on the SD card is the same.